Air versus Saline: The Effect of Tissue Expander Fill on Outcomes of Prepectoral Breast Reconstruction. Issue 1 (2nd May 2022) - Yesantharao, Pooja S.; Rizk, Nada; Martin, Shanique A.; Tevlin, Ruth; Lee, Gordon K.; Nazerali, Rahim S.
Abstract : Background: Traditionally, saline is used for intraoperative/postoperative expansion in two-stage alloplastic breast reconstruction. Recently, intraoperative expansion with air has been proposed, to reduce pressure on the mastectomy skin flap in the immediate postoperative setting. The authors examined whether the intraoperative tissue expansion medium (i.e., air versus saline) affected postmastectomy complications in two-stage prepectoral reconstruction. Methods: This was a retrospective cohort study of 87 patients (144 breasts) undergoing prepectoral breast reconstruction at the authors' institution. Patient data were abstracted from medical records. Stepwise, multivariable-adjusted logistic regression using robust variances was used to identify predictors of postmastectomy complications. Statistical and power analyses were completed. Results: Of the 87 study patients, 29 (33.3 percent) received intraoperative saline fill and 58 (66.7 percent) received air fill. Demographic/clinical data were well-matched between cohorts. Median follow-up was 165 days, and average patient age was 46.7 years. Initial tissue expander fill volumes were similar between study cohorts ( p = 0.2). The crude association between air versus saline fill on overall complication rates suggested that air-filled tissue expanders may be protective (OR = 0.4; p = 0.03), and the suggested protective effect was maintained with borderline significance even after potential confounders (i.e., American Society of Anesthesiologists class III or higher, body mass index, diabetes, mastectomy specimen weight, smoking status) were added to the model (OR = 0.4; p = 0.05). In addition, fewer complications requiring salvage reoperation were observed with air-filled tissue expanders (adjusted OR = 0.3; p = 0.02). Conclusions: The medium used for immediate intraoperative tissue expansion impacted postmastectomy outcomes in patients undergoing two-stage prepectoral breast reconstruction. The results demonstrated that air-filled tissue expanders were associated with fewer postoperative complications/salvage reoperations relative to saline-filled tissue expanders. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.